The fall of the labour income share: The role of technological change and imperfect labour markets - Francesco Carbonero; Christian J. Offermanns; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
The non-constancy of factor shares is drawing the attention of many researchers. We document an average drop of the labour share of 8 percentage points for eight European countries and the US between 1980 and 2007. We investigate theoretically and empirically two mechanisms: the substitution between Information Communication Technology (ICT) and labour and the presence of hiring costs. We find that the ICT-labour replacement is a promising channel to explain the decline of the labour share, though labour market frictions takes part of its explanatory power over. In particular, hiring costs have a bigger role in Europe than in the US. Finally, by modelling the elasticity of substitution between ICT and labour as a function of institutional and structural variables, we find that it correlates with the share of routine occupations (positively) and with the share of high-skill workers (negatively). – – Die Veränderungen in der funktionalen Einkommensverteilung erhalten in der Forschung viel Aufmerksamkeit. Wir dokumentieren einen durchschnittlichen Rückgang des labour share (Anteil des Faktors Arbeit an der Einkommensverteilung) von 8 Prozentpunkten für acht europäische Länder und die USA zwischen 1980 und 2007. Wir untersuchen theoretisch und empirisch zwei Mechanismen: Substitution zwischen Informations- und Kommunikationstechnologie (IKT) und Arbeit sowie Friktionen bei Beschäftigungsanpassungen. Wir finden, dass Substitution zwischen IKT und Arbeit wesentlich den Rückgang des labour share erklären kann. Wenn Arbeitsmarktfriktionen berücksichtigt werden, übernehmen diese allerdings einen Teil der Erklärungskraft. Insbesondere spielen Einstellungskosten in Europa eine größere Rolle als in den USA. Schließlich wird die Subsitutionselastizität zwischen IKT und Arbeit als Funktion institutioneller und struktureller Variablen modelliert und festgestellt, dass sie mit dem Anteil von Routine-Berufen positiv und mit dem Anteil hochqualifizierter Arbeiter negativ korreliert.
Keywords: E02; E25; J30; J64; O33; 330; labour share; elasticity of substitution; ICT; search and matching; job polarisation